TITO’S CONCORDAT – THE 1966 PROTOCOL ON THE NEGOTIATIONS BETWEEN YUGOSLAVIA AND THE HOLLY SEE FROM A LEGAL PERSPECTIVE - Božić, Marko D (Pravni zapisi, 2020)
The paper discusses the 1966 Protocol on the Negotiations Between Yugoslavia and the Holy See that has already been subject to several historical analyses focusing primarily on negotiations leading to it rather than the document itself. The initial hypothesis is that the legal profile of the 1966 Yugoslav Protocol may indicate its hidden political weight and a deeper historical meaning. In order to discern it, the paper examines the Protocol as an instrument of international law, aiming at explaining the way its form and substance have reflected difficulties and affected changes in relations between a Communist state and the Roman Catholic Church in Tito’s Yugoslavia. Therefore, the paper compares the 1966 Yugoslav Protocol with its Eastern-European equivalents and discusses its impact on further evolution of the Yugoslav constitutional and legal framework.
Keywords: The Holy See; 1966 Protocol; Concordat; Modus Vivendi; Yugoslavia; communism